Learning descriptive text through discovery model: VHS students' achievements and voices - Krisdianata, Yoannes Yuka; Saraini, Gayatri Enok; Enjelin, Enjelin (Universitas Negeri Semarang, 2023)
It is common that vocational high school (VHS) students are perceived as having lower language proficiency than high school students. Therefore, this study aims to determine the use of discovery learning as a learning process of descriptive text and improve student learning outcomes through the application of the discovery learning model to tenth-grade students of vocational high school students. This research is classroom action research. The data analysis technique uses quantitative descriptive data obtained from teacher observations and student work results. Data is presented in the form of numbers which are then explained descriptively. To strengthen the quantitative data, focus groups, and semi-structured interviews were conducted. Based on the research results, it is known that: First, in the student learning process, there is increasing progress from pre-cycle, cycle I, and cycle II. The process of learning descriptive text through the application of the discovery learning model is interesting and fun. The students look motivated and very enthusiastic, students become more independent, creative, and able to solve problems on their own. From the results of this research, it can be concluded that the application of the discovery learning model in learning has been proven to improve student learning outcomes.